Effectiveness of Braille Reading Training in Virtual Classroom due to Pandemic COVID-19 in Pakistan - Abdul Hamid، Sarah Blake LaRose (JIE, 2024)
Technology changes faster than many of us can keep up. Due to covid-19, progress in the utilization of technology is a significant component of Braille learning these days. The main purpose of this study was to explore the Effectiveness of Braille Reading Training in Virtual Classroom due to Pandemic COVID-19 in Pakistan. It also highlighted the impact of Covid 19 on Braille reading training and the problems of teachers and Braille learners in virtual Classes during Braille reading activities.